Study And Evaluation Of Alignment Algorithms For Biological Sequence Analysis - Basu, Kaustubh (2007)
Computational biology deals with the analysis of bio-molecules such as DNA, RNA and Protein to predict the structure and function of the unknown sequences. In order to infer the biological function of a gene or protein it encodes, similarity search between the biological sequences is performed.